COGNITIVE ASPECTS OF GRAMMAR (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the cognitive dimensions of grammar, emphasizing its role as a mental system for organizing and processing language. It examines how grammar interacts with cognitive processes like pattern recognition, memory, and conceptualization, shedding light on its generative and interpretive functions. Topics include language acquisition, where innate abilities and environmental input converge, and cognitive grammar, which links grammatical structures to mental representations of meaning. The article also highlights the influence of memory and cross-linguistic perspectives on grammatical systems, showcasing grammar's universality and adaptability. By approaching grammar through a cognitive lens, the piece provides a deeper understanding of its function as a bridge between thought and communication.